Additive effect of type 2 diabetes mellitus, sarcopenia, and hypertension on cardiovascular disease and mortality: A national-wide cohort study from China - Su, M; Yang, X; Li, T; Zhang, Y; Qiu, W; Liu, S (Journal of postgraduate medicine, 2025)
The combined impact of type 2 diabetes mellitus (T2DM), sarcopenia, and hypertension on incident cardiovascular disease (CVD) and mortality remains inconclusive. This study aimed to evaluate the additive effect of these co-morbidities on CVD and all-cause mortality among Chinese adults aged 45 years and older. A total of 12,398 participants were enrolled in the China Health and Retirement Longitudinal Study. Participants were categorized based on their T2DM, sarcopenia, and hypertension status. The study outcomes included incident CVD (including heart disease and stroke) and all-cause mortality. Multivariable logistic regression models and population attributable fractions (PAFs) were employed to investigate the associations between the coexistence of T2DM, sarcopenia, and hypertension with CVD incidence and mortality. Compared to those with none of T2DM, sarcopenia, or hypertension, participants with any one, any two, or all three of these conditions exhibited increased risks of incident CVD and higher odds of all-cause mortality. The ORs for CVD and all-cause mortality significantly increased in the groups with none, any one, any two, and all three co-morbidities. (P for trend < 0.001) These three co-morbidities collectively explained 19.1% (95% confidence interval [CI]: 15.7, 22.3) of PAF for CVD and 19.0% (95% CI: 13.5, 24.2) for mortality. The results remained generally consistent in the sensitivity analyses. Participants with the coexistence of T2DM, sarcopenia, and hypertension faced a more than two-fold increase in the risk of CVD events and mortality. The estimated PAFs indicated that preventing these three co-morbidities could be beneficial in reducing CVD incidence and all-cause mortality.